GENITAL TUBERCULOSIS MIMICKING CARCINOMA OVARY: CAN ULTRASOUND GUIDED BIOPSY BE A RESOLUTION! - Akhtar, Nosheen; Hayat, Zartaj; Nazim, Fatima (Journal of Ayub Medical College Abbottabad, 2017)
Genital tuberculosis mimicking carcinoma ovary is a well-known dilemma as there is no definitive serological or imaging modality for diagnosing abdominopelvic tuberculosis. A 20-years-old unmarried girl presented with complex adnexal mass, mild ascites and CA 125 >1000. Her staging laparotomy and frozen section was planned. Laparotomy revealed miliary tuberculosis and frozen section confirmed the diagnosis of tuberculosis. Patient was started with anti-tuberculosis treatment and follow up showed resolution of cysts. Another case is of 31 years old unmarried lady presented with history of abdominal pain. Her ultrasound revealed complex adnexal mass. CT scan revealed bilateral adnexal masses with solid and cystic lesion, ascites, para aortic lymphadenopathy; features suggestive of mitotic lesion. Her CA 125 was >1000. Family history of tuberculosis was positive. Keeping her age group and family history in view; workup of tuberculosis was performed. X ray chest was normal. Tuberculin skin test was 10mm and Quantiferon gold test was negative. In this case a decision of ultrasound guided biopsy was made. Result of biopsy showed granulomatous inflammation confirming pelvic tuberculosis. Ultrasound guided biopsy is a minimally invasive procedure with high diagnostic yield can be very helpful in such case. Clear guidelines should be developed nationally owing to the high prevalence of tuberculosis in our country to avoid unnecessary laparotomies. Keywords: Genital tuberculosis; Adnexal cyst; CA125; Ultrasound guided biopsy, Tuberculosis